2018
DOI: 10.1002/mc.22881
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induces STAT1 expression to exacerbate the IFNr‐mediated PD‐L1 axis in epidermal growth factor receptor‐positive cancers

Abstract: The epidermal growth factor (EGF) receptor (EGFR) overexpressed in many cancers, including lung and head and neck cancers, and is involved in cancer cell progression and survival. PD-L1, increases in tumor cells to evade and inhibit CD8+ T cells, is a clinical immunotherapeutic target. This study investigated the molecular mechanism of EGF on regulating PD-L1 in EGFR-positive cancers and determined potential agents to reduce PD-L1 expression. RNA sequencing (RNAseq) and bioinformatics analysis were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 49 publications
(62 reference statements)
3
29
0
Order By: Relevance
“…Coincidentally, NSCLC patients with these clinicopathologic factors were inclined to have EGFR‐activating mutations. Consistently, high PD‐L1 expression was likely to be associated with the presence of EGFR‐activating mutations in NSCLC, and increased PD‐L1 expression can be considered an independently negative prognosis indicator for NSCLC . In our study, the cell surface expression of PD‐L1 was high in both the HCC827 sensitive cell line and the H1975 resistant cell line, both of which had an EGFR‐activating mutation (a E476‐A750 deletion mutation in exon 19 for the HCC827 cell line and a L858R point mutation in exon 21 for the H1975 cell line).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Coincidentally, NSCLC patients with these clinicopathologic factors were inclined to have EGFR‐activating mutations. Consistently, high PD‐L1 expression was likely to be associated with the presence of EGFR‐activating mutations in NSCLC, and increased PD‐L1 expression can be considered an independently negative prognosis indicator for NSCLC . In our study, the cell surface expression of PD‐L1 was high in both the HCC827 sensitive cell line and the H1975 resistant cell line, both of which had an EGFR‐activating mutation (a E476‐A750 deletion mutation in exon 19 for the HCC827 cell line and a L858R point mutation in exon 21 for the H1975 cell line).…”
Section: Discussionsupporting
confidence: 76%
“…Consistently, high PD-L1 expression was likely to be associated with the presence of EGFR-activating mutations in NSCLC, and increased PD-L1 expression can be considered an independently negative prognosis indicator for NSCLC. [63][64][65] In our study, the cell surface expression of PD-L1 was high in both the HCC827 sensitive suggested that PD-L1 expression could be increased by the CD147mediated promotion of glucose metabolic reprogramming via EGFR signaling conferred by EGFR-activating mutations. Intriguingly, a preliminary study indicated that the metabolic response detected by 18 F-FDG PET/CT was predictive of early response and survival at 1 month after anti-PD1 treatment (nivolumab) in previously treated NSCLC.…”
Section: Discussionmentioning
confidence: 49%
“…PD‐1/PD‐L1 checkpoint blockades have positively changed the treatment patterns for advanced non‐small cell lung cancer (NSCLC), renal cancer, chronic Hodgkin's lymphoma, gastric cancer, urothelial cancer, cervical cancer, head and neck squamous cell carcinoma, hepatocellular carcinoma, and melanoma 10‐14 . The mechanisms of PD‐L1 expression in cancer cells involve multiple levels, including gene amplification, chromatin modification, transcription, and posttranscription 15‐19 . Oncogenic RAS signaling can upregulate PD‐L1 expression through a mechanism involving messenger RNA (mRNA) stability 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic RAS signaling can upregulate PD‐L1 expression through a mechanism involving messenger RNA (mRNA) stability 17 . Epidermal growth factor (EGF) can exacerbate PD‐L1 expression by increasing the protein levels of STAT1 to enforce the IFNr‐JAK1/2‐mediated signaling axis in cancers 18 . Song et al reported that the inhibition of PTEN upregulated PD‐L1 expression at the protein level, but not at the mRNA level, suggesting that posttranscription regulation is critical in PD‐L1 expression 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation